The impact of new information technology in the developing countries - Thorpe, Peter (SAGE Publications, 1984)
The major constraints to the use of new information tech nology in the developing countries are identified and discus ssed, and related to the setting up of a computerised biblio graphic database system. Examples of existing systems are given to provide guidelines as to how new technology can successfully be used in the developing countries despite these constraints. It is concluded that staff training, international cooperation and socio-political aspects (attitudes) are the prior ity areas for attention by the developing countries. New tech nology can be successfully introduced only if there is the political will and all involved are fully committed to the idea.